2023
DOI: 10.1097/md.0000000000035274
|View full text |Cite
|
Sign up to set email alerts
|

Adult patients with tetanus in Anhui Province of China from 2013 to 2022: A retrospective study

Dai Cheng,
Li Liang,
Hu Miaomiao
et al.

Abstract: Tetanus is a highly fatal infectious disease with an incubation period of 7 to 8 days. The aim of this study was to identify risk factors for death in tetanus patients, develop a nomogram model for predicting mortality risk. This retrospective study included tetanus patients who were admitted to the intensive care unit department between January 2013 and December 2022. The patients were divided into 2 groups based on their final outcome, namely death group and survival group. Risk factors associated with morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Post-traumatic tetanus is prevalent in rural areas, with a high misdiagnosis rate and missed diagnosis rate [18]. A retrospective study of tetanus cases in the Anhui Province of China from 2013 to 2022 showed that 97.85% of tetanus patients were over 18 years old [19]. Medical records of the hospital in Guiling, China, in 2015-2017 revealed that 94.20% of the tetanus patients were over 40 years old, and the case fatality rate was up to 37.68%, with a morbidity of 0.43/100, 000 [20].…”
Section: Introductionmentioning
confidence: 99%
“…Post-traumatic tetanus is prevalent in rural areas, with a high misdiagnosis rate and missed diagnosis rate [18]. A retrospective study of tetanus cases in the Anhui Province of China from 2013 to 2022 showed that 97.85% of tetanus patients were over 18 years old [19]. Medical records of the hospital in Guiling, China, in 2015-2017 revealed that 94.20% of the tetanus patients were over 40 years old, and the case fatality rate was up to 37.68%, with a morbidity of 0.43/100, 000 [20].…”
Section: Introductionmentioning
confidence: 99%